Immunosuppressive Phenotype of Esophagus Tumors Stroma. (20th August 2020) - Kovaleva, Olga V.; Rashidova, Madina A.; Samoilova, Daria V.; Podlesnaya, Polina A.; Mochalnikova, Valeria V.; Gratchev, Alexei
Abstract : Background . Tumor-associated macrophages (TAMs) and tumor-infiltrating lymphocytes (TILs) contribute significantly to the development of immunosuppressive properties of a tumor. In this study, we performed immunohistochemical analysis of immune cells of esophageal tumors stroma. Methods . Paraffin-embedded tissue specimens from 48 esophageal squamous cell carcinoma (ESCC) patients were retrospectively collected for immunohistochemical analysis of stromal cells. For staining of macrophages, CD68, CD163, CD206, PU.1, and iNOS were used. For T cell detection, CD8, CD3, and FOXP3 were used. Also, we performed staining for PD-L1 that can be expressed on TAMs and tumor cells. Clinicopathological and survival data were collected and analyzed using the χ 2 and Fisher exact tests, Kaplan–Meier curves, and the log-rank test. The correlation analysis was performed with Spearman's rank correlation coefficient. Results . We found that FOXP3 expression was associated with age (p = 0.042 ) and iNOS expression was associated with the disease stage (p = 0.044 ). In addition, FOXP3 and CD163 appeared to be markers of good prognosis (HR = 0.4420, p = 0.0325, and HR = 0.4447, p = 0.0456, respectively). Significant association between PU.1+ and CD68+ macrophages (r = 0.833 ; p ≤ 0.001 ) and between PU.1+ and CD163+ macrophages (r = 0.500 ; p ≤ 0.001 ) was established; positive association between PU.1 and CD206 expression was also observed (r = 0.250 ; p = 0.043 ). Conclusions . Large amounts of CD163+ macrophages and FOXP3+ Т cells appear to be markers of good prognosis of ESCC. The number of PU.1+ macrophages strongly correlates with the number of CD68+ macrophages; therefore, usage of PU.1 as a potential macrophage marker can be recommended for esophageal tumors.